The International Standard for Aureomycin - Humphrey, J. H. (1953)
In 1950, the Department of Biological Standards, National Institute for Medical Research, London, was authorized by the WHO Expert Committee on Biological Standardization to proceed with the establishment of an International Standard for Aureomycin. A 100-g batch of aureomycin was obtained and was compared with the Standard Preparation of Aureomycin of the United States Food and Drug Administration (FDA) in a collaborative assay in which six laboratories in five countries participated. In all, 30 assays were carried out; 26 of these were done by biological methods, using Sarcina lutea, Bacillus pumilus, Staphylococcus aureus, or Bacillus cereus, and the remaining four by physicochemical methods. The results were subjected to standard methods of analysis, and the overall weighted mean potency (calculated from the biological assays only) was 1.0139, with limits of error of 99.5% to 100.5%. Since the International Standard is 1.39% more potent than the FDA Standard Preparation, it is probable that the latter contains a small amount of inert material; it is also possible that the International Standard itself is not 100% pure. For most practical purposes, however, both preparations may be regarded as substantially pure, and it is considered that to alter the present practice of quoting aureomycin dosage in metric units of weight would be inadvisable. Nevertheless, since the International Standard may not be a pure substance, a unit notation—for use where required in bioassays—is desirable, and the International Unit of Aureomycin has therefore been defined as the activity contained in one microgram of the International Standard.